Coexistence of intrathyroid thymic carcinoma and papillary thyroid carcinoma: a case report and literature review - Vajihinejad, Maryam; Ataei, Ali; Pashmchi, Mohammad; Aledavoud, Ali; Zand, Vahid; Broomand, Mohammad Ali; Mohammadi, Mohammad; Reshkuiyeh, Niloofar Zare (Frontiers in Oncology, 2024)
Background: Intrathyroid thymic carcinoma (ITTC) is a rare neoplasm of the thyroid, which accounts for less than 0.15% of all thyroid malignancies. The coexistence of ITTC and papillary thyroid carcinoma (PTC) is an extremely rare condition reported only in a limited number of cases.Case summary: A 26-year-old female presented with a growing neck mass, hoarseness, and dysphagia over four months. Ultrasonography revealed that the entire left lobe and the isthmus of the thyroid were replaced with a hypoechoic mass. Moreover, it revealed two hypoechoic nodules in the right thyroid. The patient underwent a total thyroidectomy and paratracheal lymph node dissection. Histopathological examinations revealed the coexistence of ITTC and PTC in the same thyroid. In immunohistochemical analyses, the ITTC was positive for CD5, P63, CD117, and CK 5/6 and negative for thyroglobulin, calcitonin, and TTF 1. At the same time, PTC was positive for TTF 1 and thyroglobulin and negative for CD5, P63, and CK 5/6. The patient received postoperative radiotherapy and remained well with no evidence of recurrence during one month year follow-up.Distinguishing ITTC from other thyroid malignancies before the surgery is challenging due to its non-specific presentations.Therefore, the diagnosis relies on postoperative studies, especially immunohistochemistry. The recommended treatment approach to improve survival in ITTC cases is total thyroidectomy combined with cervical lymph node dissection, followed by postoperative radiotherapy. The coexistence of ITTC and PTC may indicate the similarity in the underlying mechanisms of these tumors. However, further investigations are needed to understand this potential correlation.